FENOMENA KEKERASAN, IMPAK, DAN STRUKTUR MIKRO BAJA 0.074 wt.% KARBON PASCA QUENCHING COOLANT - Basori; Agung Iswadi (Universitas Negeri Jakarta, 2022)
In this research the process of heating the steel material with a carbon content of 0.074 wt % to a temperature of 1000°C. The steel is subject to variations in holding time in the furnace for 10, 20, and 30 minutes. Then various steel that has been held at furnace quenched with coolant media. After quenching, the hardness is measured using the Vickers hardness test and tested with Charphy's impact to know the value of energy absorption. After mechanical testing, everything was finished then proceeds with the optical microscope. The longest holding time affected decreases the hardness and, the impact value will increase. Hardness and impact value are inversely proportional to the variation of holding time that has been done. The specimens formed are ferrite and pearlite based on microstructure observation.